2005
DOI: 10.1029/2004wr003562
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term flood forecasting with a neurofuzzy model

Abstract: [1] This study explores the potential of the neurofuzzy computing paradigm to model the rainfall-runoff process for forecasting the river flow of Kolar basin in India. The neurofuzzy computing technique is a combination of a fuzzy computing approach and an artificial neural network technique. Parameter optimization in the model was performed by a combination of backpropagation and least squares error methods. Performance of the neurofuzzy model was comprehensively evaluated with that of independent fuzzy and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(129 citation statements)
references
References 57 publications
1
115
1
7
Order By: Relevance
“…Các phương pháp học máy tiếp cận bài toán dự báo lưu lượng nước đổ về hồ chứa đã được nghiên cứu và đạt được nhiều kết quả khả quan [17,18,19]. Mạng nơron (neural) nhân tạo (ANN) được chứng minh bằng thực nghiệm cho thấy là một trong các phương pháp hiệu quả nhất và được dùng nhiều trong tính toán dự báo dạng chuỗi thời gian đối với bài toán thuộc dạng này [18,[20][21][22][23][24]. Trong những năm gần đây, phương pháp Deep learning (Học sâu) dựa trên nền tảng mạng nơron nhân tạo đang phát triển rất nhanh và thu hút đông đảo cộng đồng nghiên cứu tham gia.…”
Section: đặT Vấn đềunclassified
“…Các phương pháp học máy tiếp cận bài toán dự báo lưu lượng nước đổ về hồ chứa đã được nghiên cứu và đạt được nhiều kết quả khả quan [17,18,19]. Mạng nơron (neural) nhân tạo (ANN) được chứng minh bằng thực nghiệm cho thấy là một trong các phương pháp hiệu quả nhất và được dùng nhiều trong tính toán dự báo dạng chuỗi thời gian đối với bài toán thuộc dạng này [18,[20][21][22][23][24]. Trong những năm gần đây, phương pháp Deep learning (Học sâu) dựa trên nền tảng mạng nơron nhân tạo đang phát triển rất nhanh và thu hút đông đảo cộng đồng nghiên cứu tham gia.…”
Section: đặT Vấn đềunclassified
“…Neurology, Mathematics, statistics, physics, computer science and engineering are examples of mentioned sciences [5,6,7]. Most recently Multi Layer Perceptron (MLP) has been widely used to predict pollutants so that in most large cities around the world for MLP has been used to predict air pollutant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was reported that the detrimental effects of particulate matter on human health, is mostly due to being exposed to concentrations of particles. One of the most effective actions to control and reduce air pollution is to estimate the pollutants density and to describe the state of air quality in comparison with the standard conditions [7]. This paper tries to estimate and predict the air pollution of Tehran with two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Use of this technique for rainfall-runoff and river flow time series predictions has been reported by many researchers (e.g. Valenca & Ludermir, 2000;Chang & Chen, 2001Nayak et al, 2004Nayak et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%